2012
DOI: 10.3186/jjphytopath.78.293
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and plant host range of Rhizobacter dauci, causal agent of carrot bacterial gall.

Abstract: (2012). Isolation and plant host range of Rhizobacter dauci, causal agent of carrot bacterial gall. Jpn. J. Phytopathol.78: 293-300.Bacterial galls were found on roots of tomato (Solanum lycopersicum), cabbage (Brassica oleracea), shepherd's purse (Capsella bursapastoris var. pinnata), bog yellowcress (Rorippa palustris), purple deadnettle (Lamium purpureum) and corn speedwell (Veronica arvensis) in Shizuoka Prefecture from December 2007 to July 2008. Galls had formed on the main or secondary roots, and bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…In California almond orchards, C. bursa-pastoris has been infected by the bacterium Xylella fastidiosa, a cause of almond leaf scorch, usually transmitted by hemipteran vectors such as the blue-green sharpshooter Graphocephala atropunctata Signoret (Shapland et al 2006). The bacterium Rhizobacter dauci, the causal agent of carrot bacterial gall, produced galls on the roots of a wide range of host species, including C. bursa-pastoris, in Japan (Kawarazaki et al 2012). Lee et al (2016) identified nine species of sporeforming bacilli bacteria from fresh samples of C. bursapastoris in South Korea: Bacillus drentensis, B. acidiceler, B. aryabhattai, B. asahii, B. firmus, B. pseudomycoides, B. psychrodurans, B. simplex, Bacillus sp., Paenibacillus lautus, P. barcinonensis, P. tundra, and Brevibacillus reuszeri.…”
Section: Stem Diseasementioning
confidence: 99%
“…In California almond orchards, C. bursa-pastoris has been infected by the bacterium Xylella fastidiosa, a cause of almond leaf scorch, usually transmitted by hemipteran vectors such as the blue-green sharpshooter Graphocephala atropunctata Signoret (Shapland et al 2006). The bacterium Rhizobacter dauci, the causal agent of carrot bacterial gall, produced galls on the roots of a wide range of host species, including C. bursa-pastoris, in Japan (Kawarazaki et al 2012). Lee et al (2016) identified nine species of sporeforming bacilli bacteria from fresh samples of C. bursapastoris in South Korea: Bacillus drentensis, B. acidiceler, B. aryabhattai, B. asahii, B. firmus, B. pseudomycoides, B. psychrodurans, B. simplex, Bacillus sp., Paenibacillus lautus, P. barcinonensis, P. tundra, and Brevibacillus reuszeri.…”
Section: Stem Diseasementioning
confidence: 99%
“…Infected plants develop galls along the entire length of the storage roots from the crown to the root tip ( Goto and Kuwata, 1988 ). R. dauci appears to have an extremely wide host range and produces galls on the roots, stems and tubers of at least 46 plant species from 24 families, including relevant vegetables such as tomato and cabbage as well as many common weeds ( Kawarazaki et al, 2009 , 2012 ).…”
Section: Knot Knot Who’s There?mentioning
confidence: 99%